2007
DOI: 10.31421/ijhs/13/3/741
|View full text |Cite
|
Sign up to set email alerts
|

Fruit drop: The role of inner agents and environmental factors in the drop of flowers and fruits

Abstract: The basic conditions of fruit set (synchronic bloom, transfer of pollen, etc.) still do decide definitely the fate of the flower (Cano-Medrano & Darnell, 1998) in spite of the best weather conditions (Stösser, 2002). Beyond a set quantity of fruits, the tree is unable to bring up larger load. A system of autoregulation works in the background and causes the drop of a fraction of fruits in spite of the accomplished fertilisation and the equality of physiological precedents (Soltész, 1997). There are also ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 0 publications
1
30
0
2
Order By: Relevance
“…This "June" fruit drop is a common phenomenon [11] in wild blueberry as it is in apples, apricot, avocado, citrus, coffee, pears, and others [86,87]. It has been suggested that the fruit drop may be due to pollen limitation or nutrient or water stress after pollination during fruit development [88]. However, the polynomial model ( Figure 4B) suggests that increasing pollen tetrad deposition beyond the quantities that I used in my experiment may have resulted in 100% fruit set.…”
Section: Discussionmentioning
confidence: 99%
“…This "June" fruit drop is a common phenomenon [11] in wild blueberry as it is in apples, apricot, avocado, citrus, coffee, pears, and others [86,87]. It has been suggested that the fruit drop may be due to pollen limitation or nutrient or water stress after pollination during fruit development [88]. However, the polynomial model ( Figure 4B) suggests that increasing pollen tetrad deposition beyond the quantities that I used in my experiment may have resulted in 100% fruit set.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, pollinator-mediated yield is strongly conditioned by cultivar and their spatial arrangements in fields (Bell et al, 2012;Klatt et al, 2014), as well as environmental conditions and farm management practices Bos et al, 2007a,b;Groeneveld et al, 2010;Hoover et al, 2012;Lundin et al, 2013;Melathopoulos et al, 2014;Racskó et al, 2007), suggesting current estimates of D largely do not account for variation within each crop to carry fruit and seeds to harvest. This points to a more profound problem; in the IPEV calculation D is regarded as a static parameter that is unresponsive to variation within and among fields, between regions, years and, importantly, in pollinator diversity and density.…”
Section: Contingent Valuation Methods 2010mentioning
confidence: 96%
“…J. Racskó with co-authors (2008) determined relationship between premature fruit drop and amount of developed seeds in fruit. Fruits with the lowest amount of developed seeds are shedding first (Racskó et al, 2007). According to B.…”
Section: Group II Groupmentioning
confidence: 99%